Air Quality and Behavioral Impacts of Anti-Idling Campaigns in School Drop-Off Zones - Daniel L. Mendoza; Tabitha M. Benney; Ryan Bares; Benjamin Fasoli; Corbin Anderson; Shawn A. Gonzales; Erik T. Crosman; Madelyn Bayles; Rachel T. Forrest; John R. Contreras; Sebastian Hoch (Atmosphere, 2022)
Vehicle emissions are a major source of pollution in urban communities and idling may contribute up to 34% or more to local air pollution levels. Reduced idling has been found to be an effective policy tool for improving air quality, especially around schools, where it may also improve outcomes for asthmatic children. We studied two anti-idling campaigns in Salt Lake County, Utah to understand if reduced engine idling leads to behavioral change and subsequent reduction in traffic-related air pollution exposure of the related school. We found a 38% decrease in idling time following an anti-idling campaign and an 11% decrease in the number of vehicles idling at the school drop-off zones. The air quality measurements showed improvement in the middle of the campaign, but seasonal variability as well as atmospheric inversion events had substantial effects on overall ambient pollutant concentrations. This study provides an encouraging starting point to develop more effective anti-idling campaigns to protect the health of children, school staff, and the surrounding community.